Boquillas de pulverización hidráulicas para la aplicación de nematodos entomopatógenos. (2018)
Biological control is a viable alternative to chemical control; however, some methods of releasing control agents still need to be improved in order to attract the attention of producers and to reduce costs. Therefore, this work was conducted to evaluate the effects of hydraulic spray nozzles on the viability and infectivity of entomopathogenic nematodes. The experiment was conducted using a completely randomized design with 37 treatments, of which there were three controls and 34 treatments using different spray nozzles with six repetitions. A spraying table was used for the applications. The working pressure was 400 kPa for all nozzles and the solution sprayed consisted of an aqueous suspension of the nematode Heterorhabditis amazonensis MC01 at a concentration of 400 infective juveniles (IJ) mL-1. The viability of the IJ after being sprayed, as well as the infectivity of Tenebrio molitor larvae were verified. The results indicated that nematode viability was influenced by the nozzles and the living nematodes sprayed did not lose their capacity to infect the insect.